Pemanfaatan Tiktok Live Sebagai Sarana Strategi Pemasaran Dalam Meningkatkan Penjualan Pada UMKM Galaxy Picture - Alifia Salsabila; Dwi Novaria Misidawati (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
The digital age has provided an opportunity for entrepreneurs to use digital technology as a medium of promotion to broaden the reach of the market. One of the platforms used by the masters is TikTok. This app has a live streaming feature, which, if exploited optimally, has great potential as a marketing tool. So from that, this research aims to discuss the use of live ticking as a marketing medium on the UMKM Galaxy Picture. The research method used is qualitative research that approaches case studies. Data sources are obtained from primary and secondary data. Next, the data is the data is analyzed using qualitative descriptive data analysis techniques. The results of the research revealed that using a live touch for the UMKM Galaxy Picture in three months can increase sales by about 96%. The Galaxy picture makes the uniqueness and advantage of the product an advantage for the product sold and to attract consumers. The target market is all male and female segments from 18 to 46 years of age. In marketing through a live stick, UMKM Galaxy Picture applies several strategies to increase sales. Among others, live streaming is done according to the time of activity of the target market on social media, creating an attractive title to attract the market target, giving discounts in the form of vouchers or other, and live hosts use persuasive communication to persuade the target market. The Galaxy picture also has some barriers to marketing like this. However, it can be managed well by conducting an evaluation of every problem that arises to improve the quality of the business.